Snakehead fish extract as an enhancer of vascular endothelial growth factor and nitric oxide levels in cerebral angiogenesis: an insight of stroke therapy - Iskandar Nasution; Hasan Sjahrir; Syafruddin Ilyas; Muhammad Ichwan (Medicinski glasnik, 2020)
Aim: To assess the effect of snakehead fish extract administration in angiogenesis focusing on the level of vascular endothelial growth factor (VEGF), nitric oxide (NO) and VEGF receptor 2 (R2) expression is ischemic stroke models. Methods: An experimental study was conducted on 5 groups of ischemic stroke rats models: Group K-without carotid artery ligation, Group K+ with artery ligation, Group P1 with artery ligation and administration of 200 mg/day extract, Group P2 with artery ligation and 400 mg/day extract, and Group P3 with artery ligation and 800 mg/day extract. The VEGF expression and NO levels were assessed on day 3. Results: Snakehead fish extract significantly increased VEGF levels along with increasing doses, in which the highest VEGF level was observed in P3 group (361.7±40.2; p<0.001). The NO level also increased along with an increasing dose of snakehead fish extract, in which the highest NO level was found in P3 group (59.43±0.88 ?mol/gr; p<0.001). The VEGFR2 expression also increased significantly after snakehead extract administration along with increasing doses (p<0.001) in which administration of 800 mg extract yielded the highest VEGFR2 expression compared with lower doses (17.7 vs. 15.6; p<0.001) Conclusion: Snakehead fish extract administration increased angiogenesis process marked by an increased level of VEGF, NO and VEGFR2 expression in ischemic stroke rat models.
Keywords: arginine; nitric oxide; cerebral ischemia